Elevated plasma miR‐210 expression is associated with atypical genitalia in patients with 46,XY differences in sex development - Felipe Martins Elias; Mirian Yumi Nishi; Maria Helena Palma Sircili; Rafael Loch Bastista; Nathalia Lisboa Gomes; Maria Tereza Martins Ferrari; Elaine Maria Frade Costa; Francisco Tibor Denes; Berenice Bilharinho Mendonca; Sorahia Domenice (Molecular Genetics & Genomic Medicine, 2022)
Abstract Background Differences of sex development (DSD) is a term used for conditions in which the chromosomal, gonadal or phenotypical sex is atypical. 46,XY DSD patients frequently present undervirilized external genitalia. The expression of different miRNAs in many organs of the male genital system has been reported, and these miRNAs have been associated with testicular function and its disorders, but no description has been related to DSD conditions. This study aimed to evaluate the plasma expression of miR‐210 in 46,XY DSD patients who presented atypical genitalia at birth. Methods Eighteen 46,XY DSD patients who presented atypical genitalia (undescended testis and/or hypospadias, bifid scrotum or micropenis) at birth and 36 male control individuals were selected. Plasma levels of miR‐210 and reference miR‐23a were measured using RT‐qPCR and the data were analysed by the 2−ΔCt method. Results MiR‐210 plasma levels were significantly higher in 46,XY DSD patients with atypical genitalia than in male control subjects (p = 0.0024). A positive association between miR‐210 levels and the presence of cryptorchidism and hypospadias (p = 0.0146 and p = 0.0223) was found in these patients. Significantly higher levels of miR‐210 were observed in patients with 46,XY DSD and cryptorchidism than in control subjects (p = 0.0118). These results are in agreement with previous literature reports, in which increased levels of miR‐210 expression were observed in human testicular tissue from adult males with undescended testes in comparison with samples of descended testes. Conclusion Our study showed a positive association between the presence of atypical genitalia and plasma levels of miR‐210 expression in the group of patients with 46,XY DSD of unknown aetiology studied. These findings contribute to reveal a new perspective on the role of miRNAs in the development of male external genitalia and the broad spectrum of phenotypes presented by patients with 46,XY DSD.